Safety and efficacy of injection of human placenta mesenchymal stem cells derived exosomes for treatment of complex perianal fistula in non‐Crohn's cases: Clinical trial phase I. Issue 4 (2nd February 2023) - Pak, Haleh; Hadizadeh, Alireza; Heirani‐Tabasi, Asieh; Soleimani, Masoud; Asbagh, Reza Akbari; Fazeli, Mohammad Sadegh; Kazemeini, Alireza; Keshvari, Amir; Keramati, Mohammad Reza; Salahshour, Faezeh; Nazari, Hengameh; Tafti, Seyed Mohsen Ahmadi; et al.
Abstract: Background and Aim: A perianal fistula is an abnormal tract that connects anal canal to skin. Current medical and surgical interventions have a high failure rate particularly in complex and refractory cases. MSC‐derived exosomes have demonstrated immunomodulatory effects without the conventional complications; hence, in this study, we evaluated the safety of their application for complex perianal fistula. Methods: Placenta‐derived MSCs were cultured, and exosomes were isolated using ultracentrifugation. Exosome injections were administered in the operating room to 11 patients with complex perianal fistula (presence of fistulas for at least 1 year alongside medical and surgical treatment). The patients were followed for 6 months, and the patients were evaluated using physical examination, face‐to‐face interviews, and magnetic resonance imaging (MRI). Results: Among 11 patients only one did not show any improvement upon physical examination. Five patients showed complete tract resolve. While the discharge was stopped in eight patients, two patients showed only reduction. None of the patients showed any acute or latent allergic reaction or injection related complications. Conclusion: Administration of exosomes isolated from MSCs demonstrates safety and a satisfactory therapeutic effect in treatment complex perianal fistulae; therefore, it can be a candidate for future studies and might play a significant role in treatment.